Internalising Religious Moderation In Responding To The Crisis Of Intolerance And Radicalism In The World Of Islamic Education - Nizar Arwandi (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2023)
This research aims to describe the internalisation of religious moderation in Islamic education. This phenomenon will give birth to radical movements wrapped in religious values. Educators should instil moderate values in students. Seeing this, it is very necessary to practice moderation, especially in the life of the school environment in Indonesia and throughout the world by reorganising Islamic education with rahmatal lil'alamin and wasathiyyah values. The research method used is a literature study. This research concludes that intolerance and radicalism are urgent matters to be considered and internalised for students and elements of society that can later be implemented in everyday life. Religious moderation must be embedded in each individual through attitude, character, and behaviour. Addressing the urgency of religious moderation can be done through, (1) character education, providing education to educators and students about the importance of respecting differences among educators and students or ikhtilaf. Providing this education has the following learning objectives: First, students understand the urgency of religious moderation in Islamic Education. (2) A cautious attitude in understanding Islam in a kaffah manner supported by the correct methodology. (3) Strengthening the attitude of active tolerance in students.